Life Cycle Assessment of Medical Waste Management: Case Study for Istanbul - Ender Çetin; İlknur Aysel Esenlikçi Yıldız; Çiğdem Öz Yaşar; Anie Yulistyorini (Applied Sciences)
The amount of medical waste is anticipated to increase significantly with population growth. Ineffective medical waste management has resulted in adverse impacts on environmental and human health. Therefore, this study aimed to develop the current medical waste management strategy in Istanbul. GaBi Education version 7.3 was used to conduct a life cycle assessment (LCA) to compare the current medical waste management system (baseline scenario) with alternative scenarios including different proportions of waste disposal methods from an environmental perspective. Global warming, acidification, eutrophication, ozone layer depletion, freshwater aquatic ecotoxicity, and human toxicity were selected as the environmental impact categories found in CML 2001 within GaBi software. Scenarios with a higher proportion of incineration had more negative environmental impact, whereas the scenario incorporating waste segregation/minimization contributed to reducing the environmental impact. Therefore, Scenario 4 (waste segregation at the generation points/waste minimization + incineration + steam sterilization + landfill) presented the best environmental performance with the lowest total environmental impact value of 14.21% among all scenarios and was recommended as the most sustainable alternative for medical waste management in İstanbul.